Numerical and analytical simulation of ballistic projectile penetration due to high velocity impact on ceramic target - Amin Moslemi Petrudi; Khodadad Vahedi; Masoud Rahmani; MohammadAli Moslemi Petrudi (Fracture and Structural Integrity)
Simulation and analysis of the projectile impact and penetration problem and its effects are among the practical topics that can be used to design bulletproof panel and military equipment, construction of impact and penetration resistant structures, design of projectiles with appropriate penetration strength and High performance noted. One of the most important parameters affecting penetration is the impact velocity of the projectile. The mechanism of penetration varies in different speed ranges. In this paper, Ansys Autodyn software is used for intrusion simulation. The simulation carried out in this study is based on the accuracy and physical conditions of the problem and the compatibility of numerical simulation with the governing analytical relationships indicates the validity and accuracy of the assumptions made in the simulation. In this study, we selected materials such as material behavior, grating, contact surfaces, and controls, as well as collision of the blunt projectile with angles of 0º,15º,30º,45º by of high velocity impact 1000 m/s with the same mass and diameter and shape of the projectile nose and properties. Ceramic materials are discussed. The result of the numerical simulation comparison shows relatively good agreement between them.